An Efficient Synthesis of Thiazolo and Thiadiazolo Quinoxaline Derivatives in Ionic Liquid - B. Prasanna; B. Srinivas; Y. Jagannadham; Sumangala Rao (E-Journal of Chemistry, 2012)
A series of 3-substitutedphenyl-1-thia-tetrazopentaleno[1,2-b] naphthalene 4(a-d) and 2-substitutedphenyl-1-thia-pentazopentaleno[1,2-b] naphthalene 5(a-d) were synthesized via., the reaction of 2-aminothiazoles 2(a-d) and 2-aminothiadiazoles 3(a-d) with 2,3-dichloro quinoxaline 1 in ionic liquid without using any catalyst. This protocol has the advantages of easier workup, milder reaction conditions, high yields, and environmentally benign procedure over traditional methods. The synthesized compounds 4(a-d) and 5(a-d) tested for their anti-fungal activity and these compounds were characterized by IR, NMR and Mass spectral analysis.